Model identification of a micro air vehicle in loitering flight based on attitude performance evaluation - Wu, Huaiyu; Sun, Dong; Zhou, Zhaoying (IEEE transactions on robotics, 2004)
This paper presents a model identification of a micro air vehicle in loitering flight, based on the input-output data collected from flight experiments on a homemade 1-m-sized aircraft. A miniature flight-control system, which consists of the onboard and the ground sections, is equipped with a multichannel data logger associated with the data acquisition software. Modeling and performance analysis are carried out, based on the flight-test data using a system identification technique. Two fourth-order autoregressive with exogenous input (ARX) models are identified to present the attitude characteristics of the longitudinal (pitch) and the lateral (roll) control channels, respectively. The validity of the identified model is verified by both time-domain model prediction and frequency-domain spectral analysis. Based on the proposed ARX models, two compensators are further designed using a frequency-domain method, and then added to the closed-loop control systems to improve the transient performance of the pitch- and roll-control channels. Simulations and experiments demonstrate that the flight performance obtained by the proposed ARX model-based compensation control can be improved.